Optimization of Hypoxic Brain Injuries Diagnostics in Full-Term Newborns - M. S. Panova (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
The problem of early diagnosis of the central nervous system damage in newborn before the onset of clinical symptoms remains relevant at the present time.The aim of the study was to optimize the hypoxic brain damage diagnosis in full-term newborns by analyzing the concentration of cytokines in the umbilical cord blood.Materials and methods. During the first stage of the study, a prospective analysis of concentrations of interleukins (IL-1β, IL-4, IL-6, IL-8, IL-10), TNF-α and neuron-specific enolase (NSE) in the umbilical cord blood serum of full-term newborns was performed. The second stage of the study included the retrospective analysis of clinical data and instrumental research methods. The main method for diagnosing in the development of hypoxic brain damage in newborns was neurosonography.Results. The development of hypoxic brain damage is evidenced by the concentration of IL-1β over 30.3 pg/ml, IL-4 – over 1.7 pg/ml, IL-6 – over 79.4 pg/ml, IL-8 – over 107.7 pg/ml, NSE – more than 10.3 ng/ml and TNF-α – more than 1.6 pg/ml in umbilical cord blood.Conclusion. The results of the study confirmed that the comprehensive assessment of the cytokines concentration in the umbilical cord blood improves the hypoxic brain damage diagnosis in newborns. Analysis of the level of these markers immediately after the birth will optimize the management tactics of newborns who have undergone hypoxic exposure in antenatal and intranatal period.